EFFECT OF ANTIRETROVIRAL TREATMENT REGIMENS ON LIVER ENZYMES IN HUMAN IMMUNODEFICIENCY VIRUS PATIENTS - Mn, Adiga Sachidananda; S, Adiga Usha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Treatment of human immunodeficiency virus (HIV) with highly active antiretroviral therapy is complicated due to its effect on liver enzymes along with associated risk of opportunistic infection and its treatment. The objective of the study was to compare the effect of two zidovudine and lamivudine-based regimens on liver enzymes and to correlate them with age and CD4 count in HIV patients. Methods: In this retrospective study, patients who have received zidovudine+lamivudine+nevirapine (ZLN) or zidovudine+lamivudine+efavirenz (ZLE) at least for 1 year were included. Baseline, 6-month, and 1-year values of aspartate amino transferase (AST), alanine amino transferase (ALT), and CD4 count were collected. One-way analysis of variance and unpaired t-test were used to compare the difference in AST, ALT, and CD4 count value within basal, 6 months, and 1 year of two group and between the groups, respectively. Pearson's correlation was used for correlation study. Results: Elevation of AST levels in patients who had received ZLN regimen at different interval was significant statistically. There was a statistically significant elevation of ALT level at 6 months. There was no significant change in AST and ALT values in patients who had received ZLE regimen. Between the two regimens, there was statistically significant difference in AST and ALT values at 6 months and 1 year. There was no correlation between age and CD4 count with liver enzymes. Conclusion: We conclude from the study that nevirapine containing zidovudine regimen showed a slight elevation in AST. The efavirenz regimen did not show a change in AST and ALT.